1988
DOI: 10.1007/bf00291702
|View full text |Cite
|
Sign up to set email alerts
|

A frequent A?-persistence of fetal hemoglobin in northern Sardinia: its molecular basis and hematologic phenotype in heterozygotes and compound heterozygotes with ?-thalassemia

Abstract: A survey of hemoglobinopathies in northern Sardinia revealed a high frequency (0.3%) of carriers of a hematologic condition characterized by increased expression of fetal hemoglobin during adult life (hereditary persistence of fetal hemoglobin or HPFH). In spite of a normal hematologic phenotype, the heterozygous carriers for this condition display about 12% HbF, almost exclusively of the A gamma type; compound heterozygotes with beta-thalassemia have 20%-26% HbF and run a very mild clinical course. The sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 23 publications
0
3
1
Order By: Relevance
“…The corresponding genotype distributions were found to be in Hardy-Weinberg equilibrium, both for the HBG1 −222 to −225 AGCA→del polymorphism (highlanders, χ 2 = 0.62, P = 0.432; lowlanders, χ 2 = 0.01, P = 0.926) and the HBG2 −158 C→T polymorphism (highlanders, χ 2 = 0.38, P = 0.539; lowlanders, χ 2 = 1.26, P = 0.262). We did not observe, neither in the highland nor in the lowland population, the −117 G→A substitution in the HBG1 promoter (Ottolenghi et al, 1988) which is associated with increased HbF production. Alignment of genomic HBG1/HBG2 sequences of H. sapiens against chimpanzee P. troglodytes (NCBI: NW_001222274) showed that the major allele of each polymorphism, given in Table 1, was present in P. troglodytes.…”
Section: Resultscontrasting
confidence: 86%
“…The corresponding genotype distributions were found to be in Hardy-Weinberg equilibrium, both for the HBG1 −222 to −225 AGCA→del polymorphism (highlanders, χ 2 = 0.62, P = 0.432; lowlanders, χ 2 = 0.01, P = 0.926) and the HBG2 −158 C→T polymorphism (highlanders, χ 2 = 0.38, P = 0.539; lowlanders, χ 2 = 1.26, P = 0.262). We did not observe, neither in the highland nor in the lowland population, the −117 G→A substitution in the HBG1 promoter (Ottolenghi et al, 1988) which is associated with increased HbF production. Alignment of genomic HBG1/HBG2 sequences of H. sapiens against chimpanzee P. troglodytes (NCBI: NW_001222274) showed that the major allele of each polymorphism, given in Table 1, was present in P. troglodytes.…”
Section: Resultscontrasting
confidence: 86%
“…Hereditary Persistence of Fetal Hemoglobin (HPFH) is a clinically benign condition characterized by the continued expression in adult life of one, or both, of the duplicated y -globin genes which are normally expressed at significant levels in the fetal period only (1,2). Large deletions involving the adult 6and f3-globin genes (sometimes together with the fetal A 'y -globin gene) are responsible for a subclass of HPFH, in which both 'y -globin genes in cis to the deletion are usually kept active (Gly -Y -HPFH Gy Apy-thalassemia; G y -i3thalassemia in those cases in which the A 'y -gene is included in the deletion); on the other hand, point mutations in the promoter of the singly overexpressed A^j -or G 'y -globin gene have been consistently reported in a subclass of HPFH not detectable associated with deletions (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). A causal relationship of these mutations to the HPFH phenotype is strongly, though indirectly, supported by two types of genetic evidence: -the same mutation is present in HPFH 'y -globin genes of patients of dffferent ethnic origins (reviewed in refs.…”
Section: Introductionmentioning
confidence: 99%
“…It is worthy of note that a retrospective comparison of two large series of heterozygotes for Sardinian Ay GP-thalassemia ) and for Ay -117 (G+A) HPFH (Ottolenghi et al 1988) shows an overlapping in their hematological indices, hemoglobin composition and, to a lesser degree, even in their biosynthesis d n o n -a ratio values (dnon-a ranging from 0.94 to 2.27, mean 1.38; and from 0.70 to 1.27, mean 0.95, respectively).…”
Section: '-Tmentioning
confidence: 99%